The Effect of Exhibitors’ Brand Equity on Visitors’ Purchase Decision: Moderating Role of Exhibition’s Competitive Intensity - Hung, Chao-Chih; Su, Min-Jiun; Zhuang, Wen-Long (Journal of Economics and Behavioral Studies, 2016)
This study explores the effect of exhibitors’ brand equity on visitors’ purchase intention, purchase postponement, and switching intention in an international industrial fair, as well as examines the moderating effect of competitive intensity on the above relationships. This study surveyed visitors of the famous International Woodworking Machine Fair in Jakarta, Indonesia. Of the 200 surveys distributed, 138 valid questionnaires were returned, representing a response rate of 69.00%. Analytical results show that higher exhibitors’ brand equity is associated with visitors’ higher purchase intention, more prevalent purchase postponement, and stronger switching intention. Also, in a high competitive intensity environment, the level of visitors’ purchase postponement and switching intention of high brand equity products is similar. In a low competitive intensity exhibition, visitors are unlikely to postpone purchase of low brand equity products but are more likely to postpone purchase of high brand equity products. Lastly, in a low competitive intensity environment, visitors are less inclined to switch low brand equity suppliers but more likely to switch high brand equity suppliers. According to the research results, recommendations and limitations of this study are proposed.